Data : new trajectories in law - Herian, Robert (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book explores the phenomenon of data - big and small - in the contemporary digital, informatic and legal-bureaucratic context. Challenging the way in which legal interest in data has focused on rights and privacy concerns, this book examines the contestable, multivocal and multifaceted figure of the contemporary data subject. The book analyses "data" and "personal data" as contemporary phenomena, addressing the data realms, such as stores, institutions, systems and networks, out of which they emerge. It interrogates the role of law, regulation and governance in structuring both formal and informal definitions of the data subject, and disciplining data subjects through compliance with normative standards of conduct. Focusing on the 'personal' in and of data, the book pursues a re-evaluation of the nature, role and place of the data subject qua legal subject in on and offline societies: one that does not begin and end with the inviolability of individual rights but returns to more fundamental legal principles suited to considerations of personhood, such as stewardship, trust, property and contract. The book's concern with the production, use, abuse and alienation of personal data within the context of contemporary communicative capitalism will appeal to scholars and students of law, science and technology studies, and sociology; as well as those with broader political interests in this area"--
Information classification : general contents introduction -- Beautiful machines and bureaucratic dreams -- Somewhere between privacy and protection -- Being in data -- Data with subject -- Proximate data.
"Routledge Focus" -- front cover.
OCLC-licensed vendor bibliographic record.
Keywords: Databases -- Law and legislation; Data protection -- Law and legislation; Privacy, Right of; BUSINESS & ECONOMICS / E-Commerce / General (see also COMPUTERS / Electronic Commerce); COMPUTERS / Data Processing / General; COMPUTERS / Database Management / General